N‐glycan based models improve diagnostic efficacies in hepatitis B virus‐related hepatocellular carcinoma - Fang, Meng; Zhao, Yun‐Peng; Zhou, Fei‐Guo; Lu, Lun‐Gen; Qi, Peng; Wang, Hao; Zhou, Kun; Sun, Shu‐Han; Chen, Cui‐Ying; Gao, Chun‐Fang (International journal of cancer, 2010)
The early diagnosis of hepatocellular carcinoma (HCC) is of great clinical desirable due to lack of specific and sensitive markers. Alterations in the sugar chains of glycoprotein synthesized by the liver contribute to the molecular basis of abnormalities in carcinogenesis. This study aims to construct and assess the diagnostic value of N‐glycan based diagnostic model in HCC identification and follow‐up. A total of 393 subjects including HBV‐related HCC, liver fibrosis and healthy controls were recruited. Follow‐up was carried out before and after surgical treatment in HCC. N‐glycome of serum glycoprotein was profiled by DNA sequencer‐assisted fluorophore‐assisted carbohydrate electrophoresis (DSA‐FACE). Multiparameters diagnostic models were constructed based on N‐glycan markers. The result found that 2 N‐glycan structure abundances (NG1A2F, Peak 4; NA3Fb, Peak 9) were useful as N‐glycan markers. The diagnostic efficacy of the log ratio [log(p9/4)] was similar to that of AFP in differentiating HCC from fibrosis. The accuracy and sensitivity of the diagnostic model combining AFP and N‐glycan markers (Cscore B) were increased 7–10% compared with that of AFP. Log(p9/4) was more efficient in monitoring the progression of HCC with regarding to vascular invasion at improved specificity (16%) and accuracy (8%) compared with that of AFP. The N‐glycan markers were found to be changed significantly after surgical resection in HCC follow‐up. We conclude that the branching α (1,3)‐fucosylated triantennary glycan and a biantennary glycan are promising as N‐glycan markers. The diagnostic models based on the N‐glycan markers and AFP improve the efficacy in HCC diagnosis and progression monitoring.